Dynasore Protects Ocular Surface Mucosal Epithelia Subjected to Oxidative Stress by Maintaining UPR and Calcium Homeostasis - Martinez-Carrasco, Rafael (Free Radic Biol Med, 2020)
The mucosal epithelia of the ocular surface protect against external threats to the eye. Using a model of human stratified corneal epithelial cells with mucosal differentiation, we previously demonstrated that a small molecule inhibitor of dynamin GTPases, dynasore, prevents damage to cells and their transcellular barriers when subjected to oxidative stress. Investigating mechanisms, we now report the novel finding that dynasore acts by maintaining Ca(+2) homeostasis, thereby inhibiting the PERK branch of the unfolded protein response (UPR) that promotes cell death. Dynasore was found to protect mitochondria by preventing mitochondrial permeability transition pore opening (mPTP), but, unlike reports using other systems, this was not mediated by dynamin family member DRP1. Necrostatin-1, an inhibitor of RIPK1 and lytic forms of programmed cell death, also inhibited mPTP opening and further protected the plasma membrane barrier. Significantly, necrostatin-1 did not the protect the mucosal barrier. Oxidative stress increased mRNA for sXBP1, a marker of the IRE1 branch of the UPR, and CHOP, a marker of the PERK branch. It also stimulated phosphorylation of eIF2α, the upstream regulator of CHOP, as well as an increase in intracellular Ca(2+). Dynasore selectively inhibited the increase in PERK branch markers, and also prevented the increase intracellular Ca(2+) in response to oxidative stress. The increase in PERK branch markers were also inhibited when cells were treated with the cell permeable Ca(2+) chelator, BAPTA-AM. To our knowledge, this is the first time that dynasore has been shown to have an effect on the UPR and suggests therapeutic applications.